Electrode and secondary battery

By forming a polymer layer containing copolymers and inorganic particles on the electrode active material layer, the problem of reduced capacity and increased resistance of lithium-ion secondary batteries at high temperatures is solved, and the high temperature stability and charging and discharge performance of the battery are improved.

CN119137759APending Publication Date: 2024-12-13DAIKIN INDUSTRIES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037744.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-01-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The capacity of existing lithium-ion secondary batteries is easily reduced when stored at high temperatures, and the resistance increases after repeated charging and discharging, affecting the performance and safety of the battery.

Method used

A polymer layer containing copolymer and inorganic particles is formed on the electrode active material layer. The copolymer contains fluorine-containing monomer units and amide-containing monomer units. This structural construction is used to improve the high temperature stability and charging of the battery. Discharge cycle performance.

Benefits of technology

It effectively keeps the battery's storage capacity at high temperatures not easy to decrease, and the resistance is not easy to increase after repeated charging and discharging, improving the durable life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112343340000041
    Figure BDA0005112343340000041
  • Figure BDA0005112343340000042
    Figure BDA0005112343340000042
  • Figure BDA0005112343340000191
    Figure BDA0005112343340000191
Patent Text Reader

Abstract

Provided is an electrode provided with an electrode active material layer and a polymer layer formed on the electrode active material layer, in which the polymer layer contains inorganic particles and a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode and a secondary battery. Background Art

[0002] Patent document 1 describes a lithium ion secondary battery, which includes a positive electrode, a negative electrode, a polymer layer and a lithium ion permeable insulating layer, the positive electrode includes a positive electrode active material layer containing a positive electrode active material capable of inserting and deinserting lithium and a positive electrode collector, the negative electrode includes a negative electrode active material layer formed by a gas phase method and containing an alloy-based negative electrode active material and a negative electrode collector, the polymer layer is formed on the surface of the negative electrode active material layer, contains a first polymer and a first inorganic oxide particle, and the lithium ion permeable insulating layer is configured in a manner between the positive electrode and the negative electrode.

[0003] Patent Document 2 describes a composition characterized by comprising an inorganic filler, a copolymer of a fluorine-containing monomer and a polymerizable vinyl compound having an amide bond, and a solvent.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-250968

[0007] Patent Document 2: International Publication No. 2020 / 054210 Summary of the invention

[0008] Problems to be solved by the invention

[0009] An object of the present invention is to provide an electrode capable of obtaining a secondary battery whose storage capacity is unlikely to decrease even after storage at high temperatures and whose resistance is unlikely to increase even after repeated charge and discharge.

[0010] Means for solving problems

[0011] According to a first aspect of the present invention, there is provided an electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer contains a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit and inorganic particles.

[0012] Effects of the Invention

[0013] According to the present invention, it is possible to provide an electrode capable of obtaining a secondary battery whose storage capacity is unlikely to decrease even after storage at high temperatures and whose resistance is unlikely to increase even after repeated charge and discharge. DETAILED DESCRIPTION

[0014] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0015] The electrode of the present invention includes an electrode active material layer and a polymer layer formed on the electrode active material layer.

[0016] Patent document 1 states that in a lithium-ion secondary battery using an alloy-based negative electrode active material, by forming a polymer layer containing a first polymer and a first inorganic oxide particle on the surface of the negative electrode active material layer, a lithium-ion secondary battery can be obtained that has excellent battery performance such as charge and discharge cycle characteristics and output characteristics, a long service life, and very little reduction in the above-mentioned battery characteristics even when the number of charge and discharge times increases, thereby having high safety against internal short circuits, etc.

[0017] However, in the method of forming a polymer layer containing a first polymer and first inorganic oxide particles on the surface of a negative electrode active material layer as proposed in Patent Document 1, it is clear that the storage capacity is easily reduced when stored at high temperatures, and further, the increase in resistance after repeated charge and discharge of the secondary battery cannot be fully suppressed.

[0018] Therefore, in-depth research has been conducted on a method for obtaining a secondary battery whose storage capacity is not easily reduced even after storage at high temperatures and whose resistance is not easily increased even after repeated charge and discharge. As a result, it was found that by forming a polymer layer containing a copolymer and inorganic particles on an electrode active material layer, wherein the copolymer contains a fluorine-containing monomer unit and an amide bond-containing monomer unit, an electrode for a secondary battery can be obtained whose storage capacity is not easily reduced even after storage at high temperatures and whose resistance is not easily increased even after repeated charge and discharge.

[0019] That is, the electrode of the present invention is an electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer. Since the polymer layer contains a copolymer and inorganic particles, and the copolymer contains a fluorine-containing monomer unit and an amide bond-containing monomer unit, by using the electrode of the present invention as an electrode for a secondary battery, a secondary battery can be obtained whose storage capacity is not easily reduced even after storage at high temperatures and whose resistance is not easily increased even after repeated charge and discharge.

[0020] Hereinafter, embodiments of the electrode of the present invention will be described in more detail.

[0021] The electrode of the present invention includes an electrode active material layer and a polymer layer formed on the electrode active material layer.

[0022] (Polymer layer)

[0023] The polymer layer possessed by the electrode of the present invention contains copolymers and inorganic particles, and is formed on the electrode active material layer. As long as the polymer layer is formed on the electrode active material layer, it can be directly formed on the electrode active material layer without other layers, and it can also be formed on the electrode active material layer via other layers, but from the aspect of being able to fully obtain the effect brought by forming the polymer layer, it is preferably formed directly on the electrode active material layer without other layers.

[0024] (Copolymer)

[0025] The copolymer contained in the polymer layer contains a fluorine-containing monomer unit and an amide bond-containing monomer unit.

[0026] Examples of the fluorinated monomers that form the fluorinated monomer units include: (1) monomers having sp 2 Olefins of fluorine atoms bonded to hybrid carbon atoms; (2) monomers represented by the general formula: CH2=CX-COORf (wherein X is Cl, H or an alkyl group, and Rf is a fluoroalkyl group); (3) monomers represented by the general formula: CH2=CH-Rf (wherein Rf is a fluoroalkyl group); (4) monomers represented by the general formula: CH2=CH-ORf (wherein Rf is a fluoroalkyl group), etc.

[0027] Examples of the alkyl group include an alkyl group having 1 to 3 carbon atoms, and a methyl group is preferred.

[0028] The fluoroalkyl group is preferably a linear or branched fluoroalkyl group having 1 to 12 carbon atoms.

[0029] As the fluorine-containing monomer, from the viewpoint that fluorine atoms bonded to carbon atoms constituting the main chain of the polymer can be introduced into the above copolymer, thereby further improving the performance of the secondary battery, preferably (1), more preferably selected from vinylidene fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, trifluorochloroethylene, monofluoroethylene, trifluorostyrene and the general formula: CX2 = CXRf 1 (wherein, X is independently H or F, at least one of X is F, Rf 1 At least one selected from the group consisting of fluorinated monomers represented by a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms.

[0030] As the fluorine-containing monomer, from the viewpoint of further improving the performance of the secondary battery, at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene is more preferred, and tetrafluoroethylene is particularly preferred.

[0031] The amide bond-containing monomer forming the amide bond-containing monomer unit contains an amide bond and a polymerizable vinyl group. The above-mentioned amide bond refers to a bond between a carbonyl group and a nitrogen atom. Examples of the above-mentioned polymerizable vinyl group include vinyl, allyl, vinyl ether, vinyl ester, and acryloyl groups.

[0032] Examples of the amide bond-containing monomer include N-vinyl lactam compounds such as N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, and N-vinyl-enantholactam; non-cyclic N-vinyl amide compounds such as N-vinylformamide and N-methyl-N-vinylacetamide; non-cyclic N-allyl amide compounds such as N-allyl-N-methylformamide and allyl urea; N-allyl lactam compounds such as 1-(2-propenyl)-2-pyrrolidone; and acrylamide compounds such as (meth)acrylamide, N,N-dimethylacrylamide, and N-isopropylacrylamide.

[0033] Examples of the amide bond-containing monomer include

[0034] [Chemistry 1]

[0035]

[0036] (Where R 11 and R 12 are independently H or an alkyl group having 1 to 10 carbon atoms),

[0037] [Chemistry 2]

[0038]

[0039] (Where R 11 and R 12 independently represents H or an alkyl group having 1 to 10 carbon atoms).

[0040] As the monomer containing an amide bond, a monomer having a lactam ring is preferred. As the lactam ring, there is no particular limitation as long as it is a ring formed by an amide bond and a carbon atom, and it may be a monocyclic ring or a polycyclic ring, preferably a monocyclic ring. In addition, the lactam ring may have any substituent. As the lactam ring, for example, an α-lactam ring, a β-lactam ring, a γ-lactam ring, a δ-lactam ring, an ε-caprolactam ring, an ω-enantholactam ring, etc. may be cited.

[0041] The amide bond-containing monomer may have a structure in which the atomic group remaining after removing one or more hydrogen atoms bonded to the carbon atom or nitrogen atom forming the lactam ring is directly or indirectly bonded to the polymerizable vinyl group. For example, the amide bond-containing monomer may have a structure in which the atomic group remaining after removing one hydrogen atom bonded to the carbon atom or nitrogen atom forming the lactam ring is bonded to the vinyl group or the allyl group.

[0042] As the monomer containing an amide bond, from the aspect of being able to further improve the performance of the secondary battery, it is preferred that at least one selected from the group consisting of N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam and N-vinyl-enantholactam, more preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone and N-vinyl-ε-caprolactam, and further preferably N-vinyl-2-pyrrolidone.

[0043] The copolymer may contain other monomer units in addition to the fluorine-containing monomer units and the monomer units containing amide bonds. As other monomers, there is no particular limitation as long as they are monomers that can be copolymerized with the fluorine-containing monomers and the monomers containing amide bonds. As other monomer units, vinyl ester monomer units, vinyl ether monomer units, (meth) acrylic acid monomer units with polyethylene glycol in the side chain, vinyl monomer units with polyethylene glycol in the side chain, (meth) acrylic acid monomer units with long-chain hydrocarbon groups, vinyl monomer units with long-chain hydrocarbon groups, etc. can be cited.

[0044] From the perspective of further improving the performance of the secondary battery, the content of the fluorine-containing monomer unit in the copolymer is preferably 75 to 7 mol % relative to the total monomer units, and the content of the amide bond-containing monomer unit in the copolymer is preferably 25 to 93 mol % relative to the total monomer units.

[0045] The content of the fluorinated monomer unit in the copolymer is more preferably 60 mol% or less, further preferably 55 mol% or less, particularly preferably 50 mol% or less, most preferably 45 mol% or less, more preferably 15 mol% or more, further preferably 20 mol% or more, particularly preferably 35 mol% or more, and most preferably 40 mol% or more.

[0046] The content of the amide bond-containing monomer unit in the copolymer is more preferably 40 mol% or more, further preferably 45 mol% or more, particularly preferably 50 mol% or more, most preferably 55 mol% or more, more preferably 85 mol% or less, further preferably 80 mol% or less, particularly preferably 65 mol% or less, and most preferably 60 mol% or less.

[0047] The content of other monomer units in the copolymer is preferably 50 mol% or less, more preferably 35 mol% or less, further preferably 25 mol% or less, further preferably 15 mol% or less, particularly preferably 5 mol% or less, and preferably 0 mol% or more.

[0048] Furthermore, the copolymer may be a copolymer containing substantially only a fluorine-containing monomer unit and an amide bond-containing monomer unit.

[0049] The composition of the copolymer can be determined, for example, by 1 H-NMR and 19 F-NMR was used for determination.

[0050] From the perspective of further improving the performance of the secondary battery, the weight average molecular weight (in terms of polystyrene) of the copolymer is preferably 10,000 to 500,000, more preferably 15,000 or more, further preferably 20,000 or more, particularly preferably 30,000 or more, and more preferably 400,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0051] (Method for producing copolymer)

[0052] The copolymer can be suitably produced by a production method in which a fluorine-containing monomer, an amide bond-containing monomer, and, if necessary, other monomers are polymerized in a reactor.

[0053] As the polymerization method, suspension polymerization, emulsion polymerization, solution polymerization or the like can be used.

[0054] In addition, from the aspect of being able to produce copolymers with high molecular weight, among various polymerization methods, polymerization methods using fluorinated solvents are preferred. For example, copolymers can be appropriately produced by a production method in which at least a fluorinated monomer and an amide bond-containing monomer are polymerized in a fluorinated solvent to obtain a copolymer.

[0055] As the fluorinated solvent, there can be mentioned: hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc. perfluoroalkanes; CF2HCF2CF2CF2H, CF3CFHCF2CF2CF3, CF3CF2CF2CF2CF2H, CF3CF2CFHCF2CF3, CF3CFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, CF2HCF2CF2CF3, CF3CF2CF2CF2CF2 3CF2CF2CF2CF2CF2H, CF3CH(CF3)CF3CF2CF3, CF3CF(CF3)CFHCF2CF3, CF3CF(CF3)CFHCFHCF3, CF3CH(CF3)CFHCF2CF3, CF2HCF2CF2CF2CF2CF2H, CF3CF2CF2CF2CH2CH3, CF3CH2CF2CH3 and other hydrofluorocarbons; F(CF2)4OCH3, F(CF2)4OC2H5, (CF3)2CFOCH3, F(CF2)3OCH3 and other (perfluoroalkyl) alkyl ethers; CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, CF3CF2CH2OCF2CHF2 and other hydrofluoroalkyl ethers, etc.

[0056] The fluorinated solvent is preferably at least one selected from the group consisting of hydrofluorocarbons, (perfluoroalkyl)alkyl ethers and hydrofluoroalkyl ethers, and more preferably hydrofluoroalkyl ethers, since a copolymer having a higher molecular weight can be produced.

[0057] Among them, the fluorinated solvent is preferably at least one selected from the group consisting of CF3CH2CF2CH3, CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2 and CF3CF2CH2OCF2CHF2, and CF3CH2OCF2CHF2 is more preferable, and CF3CH2OCF2CHF2 is more preferable.

[0058] In the above-mentioned polymerization, a polymerization initiator, a surfactant and a chain transfer agent may be used, and conventionally known ones may be used respectively.

[0059] As the polymerization initiator, a free radical polymerization initiator can be used. As the polymerization initiator, for example, the following substances can be cited as representative examples:

[0060] Dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate;

[0061] Peroxyesters such as tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, and tert-amyl peroxypivalate;

[0062] Dialkyl peroxides such as di-tert-butyl peroxide;

[0063] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.

[0064] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).

[0065] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydro-dodecafluoroheptanoyl)peroxide, di(ω-hydro-tetrafluorooctanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-dec ... peroxide, bis(dichloropentafluorobutyryl) peroxide, bis(trichlorooctafluorohexanoyl) peroxide, bis(tetrachloroundecanoyl) peroxide, bis(pentachlorotetrafluorodecanoyl) peroxide, bis(undecanochlorotriacontanoyl) peroxide, and the like.

[0066] By carrying out the polymerization in the presence of a chain transfer agent, the solution viscosity, weight average molecular weight, etc. of the obtained copolymer can be appropriately adjusted. Examples of the chain transfer agent include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane.

[0067] The polymerization temperature is not particularly limited, but is preferably 0°C to 95°C, more preferably 15°C to 95°C, from the viewpoint of polymerization rate and cost required for temperature control.

[0068] The polymerization pressure is not particularly limited, but is preferably 0.3 MPaG to 1.5 MPaG, more preferably 0.4 MPaG or more, and even more preferably 1.0 MPaG or less, from the viewpoint of the polymerization rate and the pressure resistance of the reactor.

[0069] When the copolymer is obtained as a slurry after the completion of the polymerization, the polymer can be recovered by taking out the slurry from the reactor and washing and drying it.

[0070] (Inorganic particles)

[0071] The inorganic particles contained in the polymer layer are preferably inorganic particles containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba. The inorganic particles are preferably inorganic particles (excluding electrode active materials).

[0072] The inorganic particles are preferably at least one selected from the group consisting of metal oxide particles and metal hydroxide particles, and more preferably metal oxide particles containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba.

[0073] The metal oxide particles are preferably at least one type of particles selected from the group consisting of MgO, Al2O3, SiO2, TiO2, ZrO2 and BaO.

[0074] The metal hydroxide particles are preferably at least one type of particles selected from the group consisting of Mg(OH) 2 , Al(OH) 3 , and Zr(OH) 4 .

[0075] As the inorganic particles, at least one kind of particles selected from the group consisting of MgO, Al2O3, SiO2 and ZrO2 are preferred, and Al2O3 particles are more preferred.

[0076] The average particle size of the inorganic particles is preferably 25 μm or less, more preferably 10 μm or less, further preferably 5 μm or less, particularly preferably 1 μm or less, and preferably 0.02 μm or more. The average particle size of the inorganic particles is a value measured using a transmission electron microscope, a laser particle size distribution analyzer, or the like.

[0077] In the polymer layer, the content ratio of the copolymer to the inorganic particles [(copolymer) / (inorganic particles)] is preferably 0.1 / 99.9 to 49.9 / 50.1 in terms of mass ratio, more preferably 1 / 99 or more, further preferably 5 / 95 or more, particularly preferably 10 / 90 or more, more preferably 45 / 55 or less, further preferably 40 / 60 or less.

[0078] (Method for forming polymer layer)

[0079] The polymer layer can be formed, for example, by preparing a composition containing a copolymer and inorganic particles and applying the composition on the electrode active material layer.

[0080] The coating method is not particularly limited as long as it is a method that can cover the surface of the electrode active material layer with a polymer layer formed by the composition, and can cite, for example, a method in which the above-mentioned composition is applied to the electrode active material layer and the coating film is dried. As the coating method, more specifically, a method in which the above-mentioned composition is roll-coated on the electrode active material layer, a method in which the electrode active material layer is immersed in the above-mentioned composition, a method in which the above-mentioned composition is applied to the electrode active material layer and further immersed in a suitable coagulation solution for making can be cited. In addition, the above-mentioned composition can also be used to make a film, and the obtained film and the electrode active material layer are stacked by methods such as lamination. As a method for making a film using the above-mentioned composition, a method in which the above-mentioned composition is cast onto a film with a smooth surface such as a polyester film, an aluminum film, etc., and then peeled off can be exemplified.

[0081] The composition containing the copolymer and the inorganic particles preferably further contains a solvent.

[0082] As the solvent, for example, water; nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran, dioxane, ethyl cellosolve, methyl cellosolve, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether; aromatic hydrocarbon solvents such as xylene, toluene, and solvent naphtha; aliphatic hydrocarbon solvents such as n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, and mineral spirits; fluorine-containing solvents such as CF3CH2CF2CH3, CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, and CF3CF2CH2OCF2CHF2; mixed solvents thereof; and the like.

[0083] (Electrode Active Material Layer)

[0084] The electrode active material layer may contain an electrode active material and a binder. The electrode of the present invention may be used as a positive electrode or a negative electrode. Therefore, the electrode active material may be a positive electrode active material or a negative electrode active material. In addition, the positive electrode may include: a positive electrode active material layer containing a positive electrode active material and a binder, and a polymer layer formed on the positive electrode active material layer. The negative electrode may include: a negative electrode active material layer containing a negative electrode active material and a binder, and a polymer layer formed on the negative electrode active material layer.

[0085] The electrode usually has a current collector, and the electrode active material layer is formed on the current collector. The electrode active material layer can be formed on a single side of the current collector, or on both sides. In the case where the electrode active material layer is formed on both sides of the current collector, the polymer layer can be formed only on the electrode active material layer on a single side, or on the electrode active material layers on both sides.

[0086] Hereinafter, embodiments of the positive electrode and the negative electrode will be described in more detail.

[0087] (positive electrode)

[0088] The positive electrode comprises: a positive electrode active material layer containing a positive electrode active material and a binder, and a polymer layer formed on the positive electrode active material layer. By forming a polymer layer containing a copolymer and inorganic particles on the positive electrode active material layer, wherein the copolymer contains a fluorine-containing monomer unit and an amide bond-containing monomer unit, a secondary battery can be obtained whose storage capacity is not easily reduced even after storage at high temperature and whose resistance is not easily increased even after repeated charge and discharge.

[0089] (Positive electrode active material)

[0090] The positive electrode active material is not particularly limited as long as it can electrochemically insert and release lithium ions.

[0091] As the positive electrode active material, a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na and K is preferred, and a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na and K and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge is more preferred.

[0092] Among them, preferred positive electrode active materials are materials containing lithium and at least one transition metal, such as lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.

[0093] As the transition metal of the lithium transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples of the lithium transition metal composite oxide, lithium·cobalt composite oxides such as LiCoO2, lithium·nickel composite oxides such as LiNiO2, lithium·manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3, and substances in which a part of the transition metal atoms that will become the main body of these lithium transition metal composite oxides is replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. As the above-mentioned replaced substances, lithium·nickel·manganese composite oxides, lithium·nickel·cobalt·aluminum composite oxides, lithium·nickel·cobalt·manganese composite oxides, lithium·manganese·aluminum composite oxides, lithium·titanium composite oxides, etc., more specifically, LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2、LiMn 1.8 Al 0.2 O4、LiMn 1.5 Ni 0.5 O4、Li4Ti5O 12 、LiNi 0.82 Co 0.15 Al 0.03 O2, etc.

[0094] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu and the like are preferred. Specific examples of the lithium-containing transition metal phosphate compound include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and substances in which a part of the transition metal atoms that will become the main body of these lithium transition metal phosphate compounds are replaced by other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0095] In particular, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.82 Co 0.15 Al 0.03 O2、LiNi 0.33 Mn 0.33 Co 0.33 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2, LiFePO4.

[0096] (Adhesive)

[0097] As the binder, a polymer (excluding a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit) can be used.

[0098] As a binder, any binder can be used as long as it is a material safe for the solvent and electrolyte used in electrode manufacturing, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene, polypropylene, styrene-butadiene rubber, isoprene rubber, butadiene rubber, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, and the like.

[0099] (Conductive materials)

[0100] The positive electrode active material layer may further contain a conductive material. Examples of the conductive material include carbon materials such as graphite, carbon black, carbon nanotubes, carbon fibers, and acetylene black.

[0101] As the content of each component in the positive electrode active material layer, when the mass of the electrode active material layer is set to 100 mass%, it is preferred that the content of the positive electrode active material is 80.0 mass% to 99.8 mass%, the content of the conductive material is 0.1 mass% to 10.0 mass%, and the content of the binder is 0.1 mass% to 10.0 mass%.

[0102] The positive electrode generally further comprises a positive electrode current collector, on which a positive electrode active material layer is formed. The positive electrode active material layer may be formed on a single side of the positive electrode current collector, or may be formed on both sides. In the case where the positive electrode active material layer is formed on both sides of the positive electrode current collector, the polymer layer may be formed only on the positive electrode active material layer on a single side, or may be formed on the positive electrode active material layer on both sides.

[0103] Examples of the material of the positive electrode current collector include metals such as aluminum, titanium, and tantalum, or alloys thereof, among which aluminum or alloys thereof are preferred.

[0104] The positive electrode active material layer can be formed by conventional methods. For example, the following method can be cited: a binder, a thickener, a conductive material, a solvent, etc. are added to the positive electrode active material to prepare a slurry-like positive electrode mixture, which is applied to a collector and pressed after drying to obtain a high density.

[0105] Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, and casein.

[0106] Examples of the solvent for the positive electrode mixture include the same solvents as those that may be contained in the composition for forming the polymer layer.

[0107] (negative electrode)

[0108] The negative electrode comprises: a negative electrode active material layer containing a negative electrode active material and a binder, and a polymer layer formed on the negative electrode active material layer. By forming a polymer layer containing a copolymer and inorganic particles on the negative electrode active material layer, wherein the copolymer contains a fluorine-containing monomer unit and an amide bond-containing monomer unit, a secondary battery can be obtained whose storage capacity is not easily reduced even after storage at high temperature and whose resistance is not easily increased even after repeated charge and discharge.

[0109] (Negative electrode active material)

[0110] Examples of negative electrode active materials include thermal decomposition products of organic matter under various thermal decomposition conditions, carbonaceous materials such as artificial graphite and natural graphite that can embed / deintercalate lithium ions; metal oxide materials such as tin oxide and silicon oxide that can embed / deintercalate lithium ions; lithium metal; various lithium alloys, etc. Two or more of these negative electrode active materials can be used in combination.

[0111] The negative electrode active material is preferably a negative electrode active material containing a carbonaceous material or a negative electrode active material containing a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb, and Ti.

[0112] Examples of compounds containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti include lithium alloys containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti and lithium, and metal oxides containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti.

[0113] As the carbonaceous material, the carbonaceous material selected from the following materials has a good balance between the initial irreversible capacity and the high current density charge and discharge characteristics and is preferably:

[0114] (1) Natural graphite;

[0115] (2) Artificial carbonaceous materials and artificial graphite materials; carbonaceous materials {such as coal-based coke, petroleum-based coke, coal-based asphalt, petroleum-based asphalt, or materials obtained by oxidation of these asphalts, needle coke, pitch coke and carbon materials obtained by partially graphitizing them, furnace black, acetylene black, asphalt-based carbon fibers and other organic thermal decomposition products, carbonizable organic materials (such as coal tar pitch from soft pitch to hard pitch, or coal-based heavy oils such as dry distillation liquefied oil, straight-run heavy oils such as atmospheric residual oil and vacuum residual oil, crude oil, naphtha and other decomposition heavy oils such as ethylene tar produced as a by-product during thermal decomposition, as well as aromatic hydrocarbons such as acenaphthylene, decacyclic ene, anthracene, phenanthrene, N-ring compounds such as phenazine or acridine, S-ring compounds such as thiophene and bithiophene, biphenyl, Polyphenyls such as terphenyl, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, insolubilized products of these substances, nitrogen-containing organic polymers such as polyacrylonitrile and polypyrrole, sulfur-containing organic polymers such as polythiophene and polystyrene, natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan, and sucrose, thermoplastic resins such as polyphenylene sulfide and polyphenylene ether, thermosetting resins such as furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin, and carbonized products thereof, or solutions obtained by dissolving carbonizable organic substances in low molecular weight organic solvents such as benzene, toluene, xylene, quinoline, and n-hexane, and carbonized products thereof} carbonaceous materials heat-treated once or more at a temperature in the range of 400 to 3200°C;

[0116] (3) The negative electrode active material layer is composed of at least two or more carbonaceous materials with different crystallinity and / or a carbonaceous material having an interface in which the carbonaceous materials with different crystallinity are in contact;

[0117] (4) The negative electrode active material layer is composed of at least two or more carbonaceous materials having different orientations and / or a carbonaceous material having an interface in which the carbonaceous materials having different orientations are in contact with each other.

[0118] (Adhesive)

[0119] As the binder, a polymer (excluding a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit) can be used. Examples of the binder include the same binders as those that can be contained in the positive electrode active material layer.

[0120] The contents of the components in the negative electrode active material layer are preferably 99.9 to 80.0% by mass and 0.1 to 20.0% by mass of the binder, assuming the mass of the negative electrode active material layer is 100% by mass.

[0121] The negative electrode generally further comprises a negative electrode current collector, on which a negative electrode active material layer is formed. The negative electrode active material layer may be formed on a single surface of the negative electrode current collector, or may be formed on both surfaces. In the case where negative electrode active material layers are formed on both surfaces of the negative electrode current collector, a polymer layer may be formed only on the negative electrode active material layer on a single surface, or may be formed on the negative electrode active material layers on both surfaces.

[0122] Examples of the material of the negative electrode current collector include copper, nickel, stainless steel, etc. Among them, copper is preferred from the viewpoint of ease of processing into a thin film and cost.

[0123] The negative electrode active material layer can be formed by conventional methods. For example, the following method can be cited: a binder, a thickener, a conductive material, a solvent, etc. are added to the negative electrode active material to prepare a slurry-like negative electrode mixture, which is applied to a current collector and pressed after drying to obtain a high density.

[0124] Examples of the thickener include the same thickeners as those that can be used to form the positive electrode active material layer.

[0125] Examples of the conductive material of the negative electrode include metal materials such as copper and nickel; and carbon materials such as graphite and carbon black.

[0126] Examples of the solvent for the negative electrode mixture include the same solvents as those that may be contained in the composition for forming the polymer layer.

[0127] (Purpose of Electrode)

[0128] The electrode of the present invention can be used in an electrochemical device. As an electrochemical device, batteries such as secondary batteries and capacitors can be cited. The battery can be a primary battery, or a storage battery (secondary battery) or a storage element. The battery can also be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries having an electrolyte and a power generation element. As non-aqueous electrolyte batteries, for example, lithium ion primary batteries, lithium ion secondary batteries, nickel-hydrogen batteries, lithium ion capacitors, double-layer capacitors, etc. can be cited.

[0129] (Secondary battery)

[0130] The electrode of the present invention can be particularly suitably used as an electrode of a secondary battery. Among the secondary batteries, lithium ion secondary batteries are particularly preferred.

[0131] The secondary battery may be any of the following secondary batteries:

[0132] A secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, and comprising the electrode of the present invention as the positive electrode;

[0133] A secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, and comprising the electrode of the present invention as the negative electrode;

[0134] A secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, and comprising the electrode of the present invention as the positive electrode and the electrode of the present invention as the negative electrode.

[0135] As the non-aqueous electrolyte solution, a non-aqueous electrolyte solution prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving the electrolyte salt can be used.

[0136] There are no particular limitations on the organic solvent used to dissolve the electrolyte salt, and hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and vinylene carbonate can be used; one or more of fluorine solvents such as fluoroethylene carbonate, fluoroether, and fluorocarbonate can be used. The electrolyte can also use any of the conventionally known electrolytes, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, and cesium carbonate.

[0137] The secondary battery may have any shape, and examples thereof include cylindrical, rectangular, laminated, coin, and large shapes. The shapes and configurations of the positive electrode, negative electrode, and separator may be changed according to the shape of each battery.

[0138] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0139] <1> According to a first aspect of the present invention, there is provided an electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein the polymer layer contains a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit and inorganic particles.

[0140] <2> According to a second aspect of the present invention, there is provided the electrode according to the first aspect, wherein the fluorine-containing monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene.

[0141] <3> According to a third aspect of the present invention, there is provided the electrode according to the first aspect or the second aspect, wherein the amide bond-containing monomer has a lactam ring.

[0142] <4> According to a fourth aspect of the present invention, there is provided the electrode according to any one of the first to third aspects, wherein the amide bond-containing monomer is N-vinyl-2-pyrrolidone.

[0143] <5> According to the fifth aspect of the present invention, an electrode based on any one of the first to fourth aspects is provided, wherein the content of the fluorine-containing monomer unit of the copolymer is 75 mol% to 7 mol% relative to the total monomer units, and the content of the amide bond-containing monomer unit of the copolymer is 25 mol% to 93 mol% relative to the total monomer units.

[0144] <6> According to a sixth aspect of the present invention, there is provided the electrode according to any one of the first to fifth aspects, wherein the inorganic particles contain at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr, and Ba.

[0145] <7> According to a seventh aspect of the present invention, there is provided an electrode according to any one of the first to sixth aspects, wherein the content ratio of the copolymer to the inorganic particles [(copolymer) / (inorganic particles)] is 0.1 / 99.9 to 49.9 / 50.1 by mass ratio.

[0146] <8> According to the 8th aspect of the present invention, an electrode based on any one of the 1st to 7th aspects is provided, wherein the electrode active material layer contains an electrode active material and a binder, and the binder contains a polymer (which does not include a copolymer containing a fluorine-containing monomer unit and a monomer unit containing an amide bond).

[0147] <9> According to a ninth aspect of the present invention, there is provided the electrode according to the eighth aspect, wherein the electrode active material is a positive electrode active material.

[0148] <10> According to a tenth aspect of the present invention, there is provided the electrode according to the ninth aspect, wherein the positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K.

[0149] <11> According to the 11th aspect of the present invention, an electrode based on the 9th aspect or the 10th aspect is provided, wherein the positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na and K and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge.

[0150] <12> According to a twelfth aspect of the present invention, there is provided the electrode according to any one of the ninth to eleventh aspects, wherein the electrode active material layer further contains a conductive material.

[0151] <13> According to the 13th aspect of the present invention, an electrode based on the 12th aspect is provided, wherein, when the mass of the electrode active material layer is set to 100 mass%, the content of the positive electrode active material is 80.0 mass% to 99.8 mass%, the content of the conductive material is 0.1 mass% to 10.0 mass%, and the content of the binder is 0.1 mass% to 10.0 mass%.

[0152] <14> According to a fourteenth aspect of the present invention, there is provided the electrode according to the eighth aspect, wherein the electrode active material is a negative electrode active material.

[0153] <15> According to the 15th aspect of the present invention, an electrode based on the 14th aspect is provided, wherein the negative electrode active material is a negative electrode active material containing a carbonaceous material or a negative electrode active material containing a compound, wherein the compound contains at least one element selected from the group consisting of Si, Sn, V, Nb and Ti.

[0154] <16> According to the 16th aspect of the present invention, an electrode based on the 14th aspect or the 15th aspect is provided, wherein, when the mass of the electrode active material layer is set to 100 mass%, the content of the negative electrode active material is 99.9 mass% to 80.0 mass%, and the content of the binder is 0.1 mass% to 20.0 mass%.

[0155] <17> According to a seventeenth aspect of the present invention, there is provided an electrode according to any one of the first to sixteenth aspects, which is used in an electrochemical device.

[0156] <18> According to an eighteenth aspect of the present invention, there is provided a secondary battery including the electrode according to any one of the first to seventeenth aspects.

[0157] Example

[0158] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to these examples.

[0159] Each numerical value in the examples was measured by the following method.

[0160] <Monomer Composition of Polymer>

[0161] Using an NMR analyzer (Agilent Technologies, VNS 400 MHz), 1 H-NMR and 19 The monomer composition of the polymer was determined in a deuterated chloroform solution state by F-NMR measurement.

[0162] <Weight Average Molecular Weight>

[0163] The measurement was performed by gel permeation chromatography (GPC). AS-8010, CO-8020, columns (three GMHHR-H connected in series) manufactured by Tosoh Corporation and RID-10A manufactured by Shimadzu Corporation were used, dimethylformamide (DMF) as a solvent was flowed at a flow rate of 1.0 ml / min, and the weight average molecular weight was calculated from the measured data (reference: polystyrene).

[0164] In Examples and Comparative Examples, the following copolymers and inorganic particles were used.

[0165] (Copolymer)

[0166] ·Copolymer a (composition ratio: tetrafluoroethylene (TFE) / N-vinyl-2-pyrrolidone (VP) = 41 / 59, weight average molecular weight: 320,000)

[0167] ·Copolymer b (composition ratio: TFE / VP=38 / 62, weight average molecular weight: 240,000)

[0168] ·Copolymer c (composition ratio: TFE / VP=33 / 67, weight average molecular weight: 97,000)

[0169] · Copolymer d (composition ratio: vinylidene fluoride (VdF) / hexafluoropropylene (HFP) = 93 / 7, weight average molecular weight: 320,000)

[0170] (Inorganic particles)

[0171] Inorganic particles X: Alumina (particle size: 0.7 μm)

[0172] Inorganic particles Y: silicon dioxide (particle size: 0.6 μm)

[0173] Inorganic particles Z: zirconium dioxide (particle size: 0.4 μm)

[0174] Inorganic particles W: magnesium oxide (particle size: 0.6 μm)

[0175] Examples 1 to 7, Comparative Examples 1 to 2

[0176] <Preparation of Electrolyte>

[0177] Ethylene carbonate as a high dielectric constant solvent and ethyl methyl carbonate and dimethyl carbonate as low viscosity solvents were mixed in a volume ratio of 30:30:40, and LiPF6 was added thereto in a concentration of 1.1 mol / L to obtain a non-aqueous electrolyte.

[0178] <Production of positive electrode>

[0179] As the positive electrode active material, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 90 parts by mass, acetylene black as a conductive material 5 parts by mass, and polyvinylidene fluoride (PVdF) as a binder 5 parts by mass were mixed in N-methylpyrrolidone solvent to form a slurry. The obtained slurry was applied to one side of an aluminum foil with a thickness of 15 μm pre-coated with a conductive auxiliary agent, dried, and rolled using a press. The resultant was cut into a shape having a width of 50 mm and a length of 30 mm as an active material layer and a width of 5 mm and a length of 9 mm as an uncoated portion, as a positive electrode.

[0180] <Production of negative electrode>

[0181] 1 mass part of an aqueous dispersion of sodium carboxymethylcellulose (1 mass% concentration of sodium carboxymethylcellulose) as a thickener and a binder and 1 mass part of an aqueous dispersion of styrene-butadiene rubber (50 mass% concentration of styrene-butadiene rubber) were added to 98 mass parts of carbonaceous material (graphite), and mixed with a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil with a thickness of 10 μm and dried, and rolled using a press, and the obtained product was cut into a shape having a width of 52 mm, a length of 32 mm, and a width of 5 mm, and a length of 9 mm as an uncoated portion as an active material layer, as a negative electrode.

[0182] The positive electrode obtained above was subjected to the following treatment using the composition containing the copolymer and the inorganic particles. However, in Comparative Example 2, the positive electrode obtained above was used as it is without the following treatment.

[0183] <Coating treatment (Dip method)>

[0184] After mixing the copolymer and the inorganic particles in the component ratio shown in Table 1, the obtained mixture was mixed with HFE-347pc-f (CF3CH2OCF2CHF2) to prepare a composition having a solid content concentration of 10% by mass. After the positive electrode obtained above was immersed in the composition for 1 minute, the impregnated material was recovered from the composition. The impregnated material obtained was washed with HFE-347pc-f, the attached material attached to the surface of the impregnated material was rinsed, and the washed impregnated material was dried to obtain a positive electrode having a polymer layer formed on the positive electrode active material layer. The formation of a polymer layer on the active material layer was confirmed by scanning electron microscopy (SEM) or by measuring thickness and weight.

[0185] <Production of aluminum laminated batteries>

[0186] A positive electrode having a polymer layer (a positive electrode without a polymer layer in Comparative Example 2) and a negative electrode are placed opposite to each other with a microporous polyethylene film (diaphragm) having a thickness of 20 μm interposed therebetween, and the non-aqueous electrolyte obtained above is injected. After the non-aqueous electrolyte fully permeates the diaphragm, etc., it is sealed, pre-charged, and aged to produce a lithium-ion secondary battery (aluminum laminated battery).

[0187] <Measurement of Battery Characteristics>

[0188] The obtained aluminum laminate battery was subjected to measurement of the resistance increase rate after the high-temperature storage test and the low-temperature cycle test as follows.

[0189] <High temperature storage test>

[0190] At 25°C, the battery was charged to 4.35V at a constant current equivalent to 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Two cycles were performed to stabilize the battery. In the third cycle, the battery was charged to 4.35V at a constant current of 0.2C, and then charged at a constant voltage of 4.35V until the current value reached 0.05C, and then discharged to 3.0V at a constant current of 0.2C to obtain the initial discharge capacity. Then, the battery was charged to 4.35V at a constant current of 0.2C, and then charged at a constant voltage of 4.35V until the current value reached 0.05C, and then stored.

[0191] Here, 1C represents a current value for discharging the reference capacity of the battery in 1 hour, 5C represents a current value five times that, 0.1C represents a current value 1 / 10 of that, and 0.2C represents a current value 1 / 5 of that.

[0192] The secondary battery in the charged state after the initial characteristic evaluation was stored at high temperature at 60°C for 672 hours. After the battery was fully cooled, it was discharged at 0.5C to 3V at 25°C, then charged to 4.35V at a constant current of 0.2C, then charged at a constant voltage of 4.35V until the current value reached 0.05C, and discharged to 3.0V at a constant current of 0.2C to obtain the storage capacity.

[0193] The capacity retention rate (%) was calculated based on the following formula.

[0194] Capacity retention rate (%) = (conservation capacity) / (initial discharge capacity) × 100

[0195] <Determination of resistance increase rate after low temperature cycle test>

[0196] At 25°C, charge to 4.2V at a constant current equivalent to 0.2C, and then discharge to 3.0V at a constant current of 0.2C. Perform 2 cycles to stabilize the battery. Then, charge the secondary battery manufactured above to 4.2V at a constant current of 0.2C at -5°C, charge at a constant voltage of 4.2V until the current value reaches 0.05C, and discharge to 3.0V at a constant current of 0.2C to obtain the initial discharge capacity. Perform charge and discharge in the same way for 200 cycles.

[0197] The resistance of the battery at the time of calculating the initial discharge capacity stabilized as described above and the resistance after the cycle test were measured. The measurement temperature was set to -10° C. The resistance increase rate after the low-temperature cycle test was calculated based on the following formula.

[0198] Resistance increase rate (%) = resistance after 200 cycles (Ω) / resistance after initial discharge capacity calculation (Ω) × 100

[0199] The results are shown in Table 1.

[0200] [Table 1]

[0201] Table 1

[0202]

[0203] Examples 8 to 14, Comparative Examples 3 to 4

[0204] <Preparation of Electrolyte>

[0205] Ethylene carbonate and monofluoroethylene carbonate as high dielectric constant solvents and ethyl methyl carbonate as low viscosity solvent were mixed in a volume ratio of 30:5:65, and LiPF6 was added thereto in a concentration of 1.0 mol / L to obtain a non-aqueous electrolyte.

[0206] <Production of positive electrode>

[0207] 90% by mass of LiMn2O4 as a positive electrode active material, 5% by mass of acetylene black as a conductive material, and 5% by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in an N-methylpyrrolidone solvent and slurried. The obtained slurry was applied to one side of a 15 μm thick aluminum foil pre-coated with a conductive aid, dried, and rolled using a press. The resulting product was cut into a shape having a width of 50 mm, a length of 30 mm, and a width of 5 mm, a length of 9 mm uncoated portion as an active material layer, as a positive electrode.

[0208] <Production of negative electrode>

[0209] 1 mass part of an aqueous dispersion of sodium carboxymethylcellulose (1 mass% concentration of sodium carboxymethylcellulose) as a thickener and binder and 1 mass part of an aqueous dispersion of styrene-butadiene rubber (50 mass% concentration of styrene-butadiene rubber) were added to 98 mass parts of artificial graphite, and mixed with a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil with a thickness of 10 μm and dried, and rolled using a press, and the obtained product was cut into a shape having a width of 52 mm, a length of 32 mm, and a width of 5 mm, and a length of 9 mm as an uncoated portion as an active material layer, as a negative electrode.

[0210] The negative electrode obtained above was treated as follows using a composition containing a copolymer and inorganic particles. However, in Comparative Example 4, the negative electrode obtained above was used as it is without the following treatment.

[0211] <Coating treatment (Dip method)>

[0212] After mixing the copolymer and the inorganic particles in the component ratio shown in Table 2, the obtained mixture was mixed with HFE-347pc-f (CF3CH2OCF2CHF2) to prepare a composition having a solid content concentration of 10% by mass. After the negative electrode obtained above was immersed in the composition for 1 minute, the impregnated material was recovered from the composition. The obtained impregnated material was washed with HFE-347pc-f, thereby washing away the attached materials attached to the surface of the impregnated material, and then the washed impregnated material was dried to obtain a negative electrode having a polymer layer formed on the negative electrode active material layer. The formation of a polymer layer on the active material layer was confirmed by scanning electron microscopy (SEM) or by measuring thickness and weight.

[0213] <Production of aluminum laminated batteries>

[0214] The above-mentioned positive electrode and the negative electrode having a polymer layer (the negative electrode without a polymer layer in Comparative Example 4) are placed opposite to each other via a microporous polyethylene film (diaphragm) with a thickness of 20 μm, and the non-aqueous electrolyte obtained above is injected. After the above-mentioned non-aqueous electrolyte fully penetrates the diaphragm, etc., it is sealed, pre-charged, and aged to produce a lithium-ion secondary battery (aluminum laminated battery).

[0215] <Measurement of Battery Characteristics>

[0216] The obtained aluminum laminate battery was subjected to measurement of the resistance increase rate after the high-temperature storage test and the low-temperature cycle test as follows.

[0217] <High temperature storage test>

[0218] At 25°C, the battery was charged to 4.35V at a constant current equivalent to 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Two cycles were performed to stabilize the battery. In the third cycle, the battery was charged to 4.35V at a constant current of 0.2C, and then charged at a constant voltage of 4.35V until the current value reached 0.05C, and then discharged to 3.0V at a constant current of 0.2C to obtain the initial discharge capacity. Then, the battery was charged to 4.35V at a constant current of 0.2C, and then charged at a constant voltage of 4.35V until the current value reached 0.05C, and then stored.

[0219] Here, 1C represents a current value for discharging the reference capacity of the battery in 1 hour, 5C represents a current value five times that, 0.1C represents a current value 1 / 10 of that, and 0.2C represents a current value 1 / 5 of that.

[0220] The secondary battery in the charged state after the initial characteristic evaluation was stored at high temperature at 75°C for 528 hours. After the battery was fully cooled, it was discharged at 0.5C to 3V at 25°C, then charged to 4.35V at a constant current of 0.2C, then charged at a constant voltage of 4.35V until the current value reached 0.05C, and discharged to 3.0V at a constant current of 0.2C to obtain the storage capacity.

[0221] The capacity retention rate (%) was calculated based on the following formula.

[0222] Capacity retention rate (%) = (conservation capacity) / (initial discharge capacity) × 100

[0223] <Determination of resistance increase rate after low temperature cycle test>

[0224] At 25°C, charge to 4.2V at a constant current equivalent to 0.2C, and then discharge to 3.0V at a constant current of 0.2C. Perform 2 cycles to stabilize the battery. Then, charge the secondary battery manufactured above to 4.2V at a constant current of 0.2C at -10°C, charge at a constant voltage of 4.2V until the current value reaches 0.05C, and discharge to 3.0V at a constant current of 0.2C to obtain the initial discharge capacity. Perform charge and discharge in the same way for 200 cycles.

[0225] The resistance of the battery at the time of calculating the initial discharge capacity stabilized as described above and the resistance after the cycle test were measured. The measurement temperature was set to -20° C. The resistance increase rate after the low-temperature cycle test was calculated based on the following formula.

[0226] Resistance increase rate (%) = resistance after 200 cycles (Ω) / resistance after initial discharge capacity calculation (Ω) × 100

[0227] The results are shown in Table 2.

[0228] [Table 2]

[0229] Table 2

[0230]

Claims

1. An electrode comprising an electrode active material layer and a polymer layer formed on the electrode active material layer, wherein: The polymer layer contains a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit and inorganic particles.

2. The electrode according to claim 1, wherein The fluorine-containing monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene.

3. The electrode according to claim 1 or 2, wherein The amide bond-containing monomer has a lactam ring.

4. The electrode according to any one of claims 1 to 3, wherein The monomer containing an amide bond is N-vinyl-2-pyrrolidone.

5. The electrode according to any one of claims 1 to 4, wherein The content of the fluorine-containing monomer unit in the copolymer is 75 to 7 mol% based on the total monomer units, and the content of the amide bond-containing monomer unit in the copolymer is 25 to 93 mol% based on the total monomer units.

6. The electrode according to any one of claims 1 to 5, wherein The inorganic particles contain at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr, and Ba.

7. The electrode according to any one of claims 1 to 6, wherein The content ratio of the copolymer and the inorganic particles, that is, (copolymer) / (inorganic particles) is 0.1 / 99.9 to 49.9 / 50.1 in terms of mass ratio.

8. The electrode according to any one of claims 1 to 7, wherein The electrode active material layer contains an electrode active material and a binder, and contains a polymer as the binder, wherein the polymer does not include a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit.

9. The electrode according to claim 8, wherein The electrode active material is a positive electrode active material.

10. The electrode according to claim 9, wherein The positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na, and K.

11. The electrode according to claim 9 or 10, wherein The positive electrode active material is a positive electrode active material containing at least one alkali metal selected from the group consisting of Li, Na and K and at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge.

12. The electrode according to any one of claims 9 to 11, wherein The electrode active material layer further contains a conductive material.

13. The electrode according to claim 12, wherein When the mass of the electrode active material layer is 100 mass %, the content of the positive electrode active material is 80.0 mass % to 99.8 mass %, the content of the conductive material is 0.1 mass % to 10.0 mass %, and the content of the binder is 0.1 mass % to 10.0 mass %.

14. The electrode according to claim 8, wherein The electrode active material is a negative electrode active material.

15. The electrode according to claim 14, wherein The negative electrode active material is a negative electrode active material containing a carbonaceous material or a negative electrode active material containing a compound containing at least one element selected from the group consisting of Si, Sn, V, Nb and Ti.

16. The electrode according to claim 14 or 15, wherein When the mass of the electrode active material layer is 100 mass %, the content of the negative electrode active material is 99.9 mass % to 80.0 mass %, and the content of the binder is 0.1 mass % to 20.0 mass %.

17. The electrode according to any one of claims 1 to 16, which is used in an electrochemical device. 18 . A secondary battery comprising the electrode according to claim 1 .